Development of the post-alcohol stillage drying process on inert bodies and output of criterion dependence - Сабадаш, Сергій Михайлович; Казаков, Дмитро Дмитрович; Якуба, Олександр Радіонович (Eastern-European Journal of Enterprise Technologies, 2015)
The mechanism of the post-alcohol grain stillage drying process on inert bodies (fluoroplastic crumbs) in a fluidized bed is considered in the paper. Based on the analysis of a physical model of the process by similar transformations of the differential equation system, generalized (criterion) equation, which is post-alcohol grain stillage drying process on inert bodies in a fluidized bed with accounting grinding and abrasion of the material from the inert body surface was obtained. As a result of the pilot study, the explicit form of the heat transfer equation for the post-alcohol grain stillage drying process on inert bodies in a fluidized bed was obtained. The first series of experiments served to determine the functional relationship between the Nu and Gu criteria at constancy in all other criteria. The next series was carried out at different heights of dense layers of inert bodies with the same initial moisture content. The third series of experiments was performed to identify the impact of the Re criterion on the stillage drying process speed.